Pengaruh Pengetahuan Produk Terhadap Minat Menabung di Bank Syariah Indonesia (BSI) - Hendra Novian; Muhamad Wardany Anwar; Fauzi Fauzi; Rita Irviani (Jurnal Ilmiah Ekonomi Islam, 2023)
Public interest in saving is the most basic thing for banks because it can help grow the success of banks, while customer knowledge about savings products will be a factor that influences customer interest in saving. The lack of socialization to the public or customers in introducing Islamic bank products, especially savings products, causes the public or customers to understand less about existing savings products. The purpose of this research is to determine the extent of the influence of product knowledge on interest in saving at Bank Syariah Indonesia (BSI) Kalirejo Central Lampung Cash Office in 2022. This type of research is a descriptive research type and uses a quantitative approach method with the population, namely customers who save at Bank Syariah Indonesia (BSI) Kalirejo Central Lampung Cash Office. This research is a study that uses descriptive research and quantitative approach methods with the population, namely customers who save at Bank Syariah Indonesia (BSI) Kalirejo Cash Office, Central Lampung. The sampling technique used Probability Sampling technique with Simple Random Sampling method with Slovin formula as many as 99 customers. Data collection techniques using questionnaires (questionnaires), observation, interviews and documentation. Based on the results of the study, it can be concluded that the influence of knowledge of each type of savings product has a positive effect on interest in saving at Bank Syariah Indonesia (BSI) Kalirejo Cash Office, Central Lampung. This is evidenced by the results of the joint test (T-test), namely the acquisition of a significant value of 0.000